Design and Development of A Patient Lifter For Brachytherapy Procedures in Cervical Cancer Treatment - Kurniawan, Rudy; BE, Marsum; Masrochah, Siti; Darmini, Darmini; Kartikasari, Yeti (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
The role of a patient lifter in brachytherapy is crucial for ensuring safe and efficient patient transfer during treatment. The use of fabric slings for patient transfer in brachytherapy at MRCCC Siloam Hospitals Semanggi is considered ineffective as it requires at least 6-7 medical staff to move a patient. The development of medical devices, such as brachytherapy patient lifters, is critical for maintaining safety, as any failure or malfunction can cause serious injuries to both medical personnel and patients. This study aims to design a brachytherapy transfer table and evaluate its effectiveness in minimizing physical strain on healthcare workers during patient transfers. Research methods implementing a rigorous development process is essential to minimize the risk of failure by ensuring that validation and verification activities are conducted objectively, reproducibly, and are well documented. This research introduces an approach based on the formal R&D Borg and Gall method for developing brachytherapy patient lifters. Results Functional tests demonstrated the overall success of the brachytherapy patient transfer table, with a 100% validity rating from five experts. The test results showed a significant value of 0.000, less than 0.05, indicating a significant difference between conditions before and after the design of the patient transfer table. The development of the brachytherapy patient transfer table has been highly successful and effective at MRCCC Siloam Hospitals Semanggi. The device also holds potential for further development in studies with larger sample sizes.